Further evidence for the efficacy of an evidence-based, small group, literacy intervention program for young struggling readers. Issue 1 (2nd January 2017) - Wheldall, Kevin; Wheldall, Robyn; Madelaine, Alison; Reynolds, Meree; Arakelian, Sarah
Abstract: An earlier series of pilot studies and small-scale experimental studies had previously provided some evidence for the efficacy of a small group early literacy intervention program for young struggling readers. The present paper provides further evidence for efficacy based on a much larger sample of young, socially disadvantaged, at-risk readers. The participants comprised 14 successive intakes of Year 1 and Year 2 students into small group remedial literacy intervention programs hosted by two charitably run tutorial centres. In each semester, over the years 2005–2011, eight students (on average) attended each centre for one hour, for four days per week, for 15 weeks. Pre- and post-test assessment data on eight measures of early literacy performance were available on up to 194 students who completed the program. Substantial and statistically significant gains were evident on all literacy measures with large effect sizes. These results provide further evidence for the efficacy of the small group literacy intervention program.